The Long and Winding Road of EU-Turkish Relations after Copenhagen - Riemer, Andrea K. (Études helléniques / Hellenic Studies, 2003)
Europe and the European Union have reached a multiple turning point with the latest enlargement round. The Union, which started as a peace project after World War II, faces its greatest challenges within a rapidly changing environment. There is no other country that has srruggled for so many years to become 'part of the party' like Turkey. This article provides a historical overview and analyzes Turkey's European course. It places some emphasis on recent developments, including the latest Regular Report which was issued by the EU on Turkey's progress toward accession (October 2002). Finally, the results of the Copenhagen Summit (December 2002) and their possible consequences for Euro-Turkish relations are discussed.